2011
DOI: 10.1016/j.jcin.2011.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Regadenoson for Assessing Fractional Flow Reserve

Abstract: Our results suggest that a single IV bolus of regadenoson is as effective as an intravenous infusion of adenosine for measuring FFR and, given its ease of use, should be considered for FFR measurement in the catheterization laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 40 publications
1
44
0
4
Order By: Relevance
“…The authors demonstrated that this upregulated CD73 can be exploited to convert an inactive A 2A receptor agonist precursor into its active anti-inflammatory analog selectively at the site of inflammation, where the CD73/A 2A receptor axis was induced [57]. The advantage of converting this prodrug as a local effect in the joints was the reduction in side effects that are normally present when A 2A agonists are administered systematically [107,108]. …”
Section: Regulation Of Immunity By Cd39 and Cd73 In Autoimmune Diseasesmentioning
confidence: 99%
“…The authors demonstrated that this upregulated CD73 can be exploited to convert an inactive A 2A receptor agonist precursor into its active anti-inflammatory analog selectively at the site of inflammation, where the CD73/A 2A receptor axis was induced [57]. The advantage of converting this prodrug as a local effect in the joints was the reduction in side effects that are normally present when A 2A agonists are administered systematically [107,108]. …”
Section: Regulation Of Immunity By Cd39 and Cd73 In Autoimmune Diseasesmentioning
confidence: 99%
“…If necessary, the pressure wire can be Table 1 and for further discussion refer to the literature. [15][16][17][18] Clinical Applications of FFR Initially, FFR was used to investigate the functional significance of intermediate lesions, 4 over time it has been validated as useful in most clinical and angiographic conditions encountered in the catheterization laboratory. FFR has been well validated in multivessel disease, left main disease, ostial lesions, tandem lesions, diffuse disease, unstable angina pectoris and non-STEMI.…”
Section: Practical Set-up and Recommendationsmentioning
confidence: 99%
“…15 The estimated SD of the mean FFR value is 0.1 based on previous studies. [16][17][18][19] The sample size, 50, will give a 95% CI of 95% limits of agreement (LOA) about ±0.048, 20 which is sufficiently narrow and appropriate to assess the similarities with adequate accuracy.…”
Section: Sample Size Calculationmentioning
confidence: 99%